2014
DOI: 10.1590/s1413-82712014000100014
|View full text |Cite
|
Sign up to set email alerts
|

O conceito de felicidade em crianças

Abstract: Com o intuito de contribuir para a compreensão do bem-estar subjetivo e o aprimoramento dos processos de avaliação da qualidade de vida subjetiva infantil, este estudo buscou conhecer o conceito de felicidade em crianças. Participaram 200 crianças (52,5% meninas) de 5-12 anos, estudantes de escolas públicas e privadas de Porto Alegre, que responderam individualmente sobre o que pensam sobre a palavra felicidade e como definem felicidade. As respostas foram analisadas por análise de conteúdo, e comparações fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
2
17
0
6
Order By: Relevance
“…This is surprising given that adolescents compared to children tend to give more importance to relationships with peers rather than family (e.g., Fuligni & Eccles, 1993;Greenberg, Siegel, & Leitch, 1983). The obtained results are in line with the study by Giacomoni et al (2014), as children aged 11-12 mentioned family and peers to same extent. From a cultural psychological perspective, this effect might be due to collectivism which may override the developmental effect.…”
Section: Children's and Adolescents' Conceptions From The Categories supporting
confidence: 61%
See 4 more Smart Citations
“…This is surprising given that adolescents compared to children tend to give more importance to relationships with peers rather than family (e.g., Fuligni & Eccles, 1993;Greenberg, Siegel, & Leitch, 1983). The obtained results are in line with the study by Giacomoni et al (2014), as children aged 11-12 mentioned family and peers to same extent. From a cultural psychological perspective, this effect might be due to collectivism which may override the developmental effect.…”
Section: Children's and Adolescents' Conceptions From The Categories supporting
confidence: 61%
“…Chaplin (2009) found gender differences when children elaborated on the causes of happiness. Giacomoni et al (2014) also found differences between girls' and boys' conceptualizations of happiness. Yet, previous research on adults' conceptions of happiness did not find gender differences (Lu & Gilmour, 2004).…”
Section: Age and Gender Differences In The Conceptualizations Of Happmentioning
confidence: 85%
See 3 more Smart Citations